Disseminated (miliary) abdominal tuberculosis after laparoscopic gastric bypass surgery. (12th May 2011) - Alhajri, Khalid; Alzerwi, Nasser; Alsaleh, Khalid; Yousef, Hussam Bin; Alzaben, Mohamed
Abstract : The development of disseminated (miliary) abdominal tuberculosis (TB) in patients following operations which affect their immunity, such as laparoscopic gastric bypass, is rare. The authors report the case of middle aged woman, who a few months after undergoing laparoscopic gastric bypass surgery for morbid obesity (body mass index 49), presented with generalised fatigability and abnormal liver function. A CT scan of the abdomen was suggestive of miliary TB. The patient developed acute abdomen pain. Intraoperative findings included perforated stomal ulcers at the gastrojejunostomy, diffuse micronodular involvement of the liver and spleen and thickened omentum. The perforation was closed and liver and omental biopsies were taken. Histology results from the liver and omentum revealed necrotising granulomatous inflammation suggestive of TB. Abdominal TB is a relatively rare manifestation of extrapulmonary TB. However, this diagnosis should be considered in patients immunocompromised due to immunosuppressive medication or operations affecting their nutrition. Early diagnosis and effective treatment of abdominal TB may decrease morbidity and mortality in such patients.